The role of pelvis-thorax coupling in controlling within-golf club swing speed - Lamb, P. F.; Pataky, T. C. (Journal of Sports Sciences, 2019)
Pelvis-thorax coordination has been recognised to be associated with swing speed. Increasing angular separation between the pelvis and thorax has been thought to initiate the stretch shortening cycle and lead to increased clubhead speed. The purpose of this study was to determine whether pelvis-thorax coupling played a significant role in regulating clubhead speed, in a group of low-handicap golfers (mean handicap = 4.1). Sixteen participants played shots to target distances determined based on their typical 5- and 6-iron shot distances. Half the difference between median 5- and 6-iron distance for each participant was used to create three swing effort conditions: "minus", "norm", and "plus". Ten shots were played under each swing effort condition using both the 5-iron and 6-iron, resulting in six shot categories and 60 shots per participant. No significant differences were found for X-factor for club or swing effort. X-factor stretch showed significant differences for club and swing effort. Continuous relative phase (CRP) results mainly showed evidence of the stretch shortening cycle in the downswing and that it was more pronounced late in the downswing as swing effort increased. Substantial inter-individual CRP variability demonstrated the need for individual analyses when investigating coordination in the golf swing.